2006
DOI: 10.1073/pnas.0511290103
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein (PrP c ) positively regulates neural precursor proliferation during developmental and adult mammalian neurogenesis

Abstract: neural development ͉ neural precursor ͉ subventricular zone ͉ dentate gyrus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
252
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(283 citation statements)
references
References 26 publications
22
252
2
7
Order By: Relevance
“…In the adult, PrP c is not expressed by proliferating cells in the subventricular zone of the lateral ventricle (Steele et al, 2006). (Steele et al, 2006). Surprisingly, previous in vitro studies showed that PrP c -deficient neural cell lines derived from embryonic hippocampus display higher proliferative rates than WT cells in culture (Kim et al, 2005).…”
Section: However Contradictory Results Using Other Neoplastic and VImentioning
confidence: 98%
See 2 more Smart Citations
“…In the adult, PrP c is not expressed by proliferating cells in the subventricular zone of the lateral ventricle (Steele et al, 2006). (Steele et al, 2006). Surprisingly, previous in vitro studies showed that PrP c -deficient neural cell lines derived from embryonic hippocampus display higher proliferative rates than WT cells in culture (Kim et al, 2005).…”
Section: However Contradictory Results Using Other Neoplastic and VImentioning
confidence: 98%
“…In mice, PrP c expression starts during development around embryonic day E8,5-9 in postmitotic neurons (Miele et al, 2003) and around day E13,5-16,5 in specific nonneuronal populations (Manson et al, 1992). In the adult, PrP c is not expressed by proliferating cells in the subventricular zone of the lateral ventricle (Steele et al, 2006). (Steele et al, 2006).…”
Section: However Contradictory Results Using Other Neoplastic and VImentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were obtained on a mixed 129SvEv ϫ BALB/c strain background and were crossed once to C57BL/6J and maintained by intercrossing mice heterozygous for the HSF1 deletion allele. The titering of the infectivity of samples used Tga20 recipient mice that had been backcrossed to C57BL/6J for 5-6 generations and bred onto a WT PrP genome (55).…”
Section: Methodsmentioning
confidence: 99%
“…Sa fonction semble liée à l'activité synaptique, l'adhé-rence cellulaire et la poussée neuritique en association avec d'autres molécules (LRP, Laminine, N-CAM) [40][41][42]. Récemment, il a même été montré que la PrP régulerait la prolifération des précurseurs neuraux durant le développement et lors de la neurogenèse adulte [43] ainsi que la prolifération des cellules souches hématopoïétiques [44]. Aussi, la modification des fonctions physiologiques de la PrP C dans les cellules neuronales au cours de l'infection pourrait expliquer les altérations neuronales observées [56].…”
unclassified